2016
DOI: 10.3390/ijerph13060621
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Fraction Particle Matter and Exhaled Nitric Oxide in Non-Asthmatic Children

Abstract: Coarse particle matter, PMcoarse, is associated with increased respiratory morbidity and mortality. The aim of this study was to investigate the association between short-term changes in PMcoarse and sub-clininal airway inflammation in children. Healthy children aged 11 years from two northern Swedish elementary schools underwent fraction of exhaled nitrogen oxide (FENO) measurements to determine levels of airway inflammation twice weekly during the study period from 11 April–6 June 2011. Daily exposure to PMc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
3
0
1
Order By: Relevance
“…It could be speculated that school children with asthma and atopic condition had a high potential in elevating FeNO levels in relation to PM 10 and PM 2.5 exposure above the UCL inside their classrooms. A similar prediction was reported by Carlsen et al (2016) determined that particles represent the major contributor to elevate the FeNO levels among children. Liu et al (2015) also reported that school children who study in urban area and exposed to a high concentrations of PM 10 , SO 2 , formaldehyde and acetaldehyde showed significantly increased FeNO levels in asthmatic group.…”
Section: Discussionsupporting
confidence: 86%
“…It could be speculated that school children with asthma and atopic condition had a high potential in elevating FeNO levels in relation to PM 10 and PM 2.5 exposure above the UCL inside their classrooms. A similar prediction was reported by Carlsen et al (2016) determined that particles represent the major contributor to elevate the FeNO levels among children. Liu et al (2015) also reported that school children who study in urban area and exposed to a high concentrations of PM 10 , SO 2 , formaldehyde and acetaldehyde showed significantly increased FeNO levels in asthmatic group.…”
Section: Discussionsupporting
confidence: 86%
“…The result showed that there was inflammation in the airways and the average value was above the threshold of 50 ppb, which could reflect a high degree of inflammation. Liu et al [ 41 ] and Carlsen et al [ 42 ] reported that there was a significantly positive relationship between the FeNO levels and almost all pollutants, namely PM 10 , PM 2.5 , SO 2 , NO 2 , CO, and VOCs. This advocates a relationship between the high levels of all pollutants measured inside the classroom of urban schools and the high levels of FeNO among school children in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fractioned exhaled nitric oxide (FeNO) is considered a simple and useful biomarker of airways inflammation (14). Its increase, related to exposure to particulate matter, was observed among others in studies conducted in healthy adult volunteers (15) and in healthy school children (16). Other study, that took into consideration chemical composition of PM 2,5 , revealed that FeNO increase showed the strongest correlation with the concentration of organic and elemental carbon (organic carbon -OC, elemental carbon -EC), NO3(-), and NH4(+).…”
Section: Patomechanizm Oddziaływania Zanieczyszczeń Powietrzamentioning
confidence: 98%
“…Wskaźnikiem uważanym za przydatny i prosty marker zapalenia w drogach oddechowych jest tlenek azotu w powietrzu wydychanym (FeNO) (14). Wzrost jego stężenia w odpowiedzi na narażenie na pył zawieszony wykazano między innymi w badaniach prowadzonych na zdrowych ochotnikach dorosłych (15) oraz wśród zdrowych dzieci szkolnych (16). W innym badaniu biorącym pod uwagę skład chemiczny pyłu PM 2,5 zaobserwowano, że zwiększenie FeNO najlepiej korelowało ze stężeniem węgla organicznego i elementarnego (organic carbon -OC, elemental carbon -EC), NO3(-) i NH4(+).…”
Section: Patomechanizm Oddziaływania Zanieczyszczeń Powietrzaunclassified